Facial thermography for assessment of workload in safety critical environments - Marinescu, Adrian Cornelius (2018)
The fast changing modern world is placing humans in positions we have not had time to evolve and adapt to by natural means, we are thus faced with the task of understanding our abilities and limitations, at both a physical and mental levels and design the world around us with these in mind. This is in line with the aim of the discipline of ergonomics (or human factors), to "optimize human well-being and overall system performance by contributing to the design and evaluation of task, jobs, products, environments and systems" (International Ergonomics Association 2014). This is a large task, spanning multiple other disciplines. The research presented in this thesis is in the area of workload, a concept used to describe the interaction between a task and an operator in terms of demand, perception of task and performance. Many tools and methods have been developed aiming at measuring workload, ranging from subjective measures, primary and secondary task measures, task analysis and physiological measures. The main focus of this research is on physiological methods of assessing workload in safety critical environments. Within the domain of physiological methods for workload assessment, many techniques have been explored over the years and will be presented in the thesis with their advantages and disadvantages. Despite all the efforts made to develop a reliable physiological measurement assessment method for workload, further research is needed; the research presented here focuses on facial thermography as a non-invasive, real-time assessment method for workload, coupled with other physiological measures such as heart rate, breathing rate and pupil diameter. The human physiological response to changes in workload has been examined in three studies which also explore the use of multiple physiological measures as a means of estimating the level of workload. While two of the studies were performed in laboratory conditions having students as participants, a third study was performed in an ecologically valid helicopter simulator in order to test the physiological reactions of highly trained individuals to changes in workload. The results indicate that facial thermography, especially nose area temperatures, as well as pupil diameter respond well to changes in workload and could be used as a noninvasive, real-time method of estimating workload. The flight simulator study revealed that even highly trained individuals have similar responses to changes in demand as the general public. This thesis contributes to the measurement and assessment of workload by using physiological measures, especially facial thermography and presenting the relative contribution of each of the measures in both laboratory and real-life scenarios.